The worldly philosophers : the lives, times and ideas of the great economic thinkers - Heilbroner, Robert L. (New York : Simon and Schuster, 1961)
This is a book about a handful of men with curious claim to fame. By all the rules of schoolboy history books, they were nonentities: they commanded no armies, sent no men to their deaths, ruled no empires, took little part in history-making decisions.
I. Introduction -- II. The economic revolution -- III. The wonderful world of Adam Smith -- IV. The gloomy world of Parson Malthus and David Ricardo -- V. The beautiful world of the utopian socialist -- VI. The inexorable world of Karl Marx -- VII. The Victorian world and the Underworld of economics -- VIII. The savage world of Thorstein Veblen -- IX. The sick world of John Maynard Keynes -- X. The modern world -- XI. Beyond the economic revolution.
Includes index.
Keywords: ECONOMICS; ECONOMIC -- HISTORY